Development of multi-criteria decision support system (DSS) coupled with GIS for identifying optimal locations for soil aquifer treatment (SAT) facilities - Tsangaratos, P.; Pizpikis, T.; Vasileiou, E.; Pliakas, F.; Schuth, C.; Kallioras, A. (Bulletin of the Geological Society of Greece, 2013)
Managed Aquifer Recharge is a wide-spread well-established groundwater engineering method which is largely seen as an alternative potential major source for water and this conclusion becomes even more pronounced in semi-arid and/or arid areas, such as the Mediterranean Basin. The process of site selection for the installation of a MAR facility is of paramount importance for the feasibility and effectiveness of the project itself, especially when the facility will include the use of waters of impaired quality as a recharge source. The main objective of this study is to present the developed framework of a multicriteria Decision Support System (DSS) that integrates within a dynamic platform: the main groundwater engineering parameters associated with MAR applications together with the general geographical features which determine the effectiveness of such a project. The proposed system will provide an advanced coupled DSS-GIS tool capable of handling local MAR-related issues -such as hydrogeology, topography, soil, climate etc., and spatially distributed variables -such as societal, economic, administrative, legislative etc., with special reference to Soil-Aquifer- Treatment technologies. The new SAT-selection tool in question is integrated in ArcGIS software -within a user friendly environment- where data can be processed and displayed using Arc tools for spatial analysis.